Analisis makna konotatif dalam lirik lagu “Dreamers” fifa world cup 2022 - Fauziyah, Ely; Jazilah, Ela; Ifawati, Nur Ila (Universitas Lampung, 2024)
This research aims to describe the connotative meaning of the Dreamers song lyrics at the 2022 FIFA World Cup opening ceremony. This study uses descriptive qualitative research methods. The object of this research is the video clip of the Dreamers song on the FIFA YouTube channel with Dreamers song lyrics as the data. The Dreamers song was chosen because it is specifically created to welcome the 2022 World Cup, held every four years. Data was collected using the watch, listen, and note techniques. To interpret the data, researchers used the Miles and Huberman data analysis technique, which consists of the data condensation, data presentation, and conclusion. This research shows that the Dreamers song lyrics have a positive connotative meaning. The positive connotation meanings in the Dreamers song lyrics were found in 12 words consisting of the phrase dreamers, believe, keep, invited, come, gather 'round, respect, نتجمع, نتكاتف و نرفع ,نتعاون ونحققو نتحد و نتجاوز. Keywords: Connotative, dreamers, positive